Naja Kaouthia Snake Bite: Case Report - Ahmad, Bahtiar; Rehatta, Nancy Margarita (JAI (Jurnal Anestesiologi Indonesia), 2024)
Background: Snakebites prevalent globally, pose a severe threat, especially in resource-limited regions. The impact is substantial, affecting millions annually, with a significant number of fatalities.Case: A 37-year-old man experienced deterioration leading to cardiac arrest after being bitten by a Naja Kaouthia snake. Adequate management in the intensive care unit (ICU), including antivenom administration, restored the patient's condition to return of spontaneous circulation (ROSC).Discussion: Snake venom causes various symptoms, from tissue damage to breathing and heart issues. Treating with antivenom, specifically from horses, can neutralize the venom's effects, as shown in studies. This treatment is effective for Naja Kaouthia bite.Conclusion: Quick treatment with antivenom partially neutralized the venom, showing how important antivenom is for treating snakebites.